Evaluasi penerapan direct production cost pada PT. Fortuna Inti Alam - Makakombo, Olivia Natalia; Pusung, Rudy J.; Lintong , Diana N. (Manajemen Bisnis dan Keuangan Korporat, 2024)
The direct production cost is the cost that directly forms the production output. The direct production cost is comparable to the direct costing method, which is a method for calculating production costs that solely allocates variable costs directly linked to the product. This study will evaluate the application of direct production cost at PT. Fortuna Inti Alam. This study employs a descriptive qualitative research method. The results clearly show that production costs at PT. The direct costing method, as applied by Fortuna Inti Alam, allocates all costs incurred within the company, resulting in a total production cost of Rp2,838,108,539. The direct costing method, as outlined in theory, which includes only variable costs or those directly related to the product, results in a total production cost of Rp2,492,318,866. This calculation reveals a difference in total production costs amounting to Rp345,789,673, indicating that the production cost calculated using the theoretical direct costing method is lower than that used by the company.